Mechanical Properties of Concrete Made with Recycled Concrete Aggregates with Addition of Steel Fibres - لما سيد أحمد, (Latakia University Journal -Engineering Sciences Series, 2022)
In the building process, the recycling of aggregates arising from building and demolition debris is one of the best alternatives to maintain the environment and the areas needed to bury these debris. It also helps to preserve natural concrete sources from depletion efficiently. The use of recycled aggregates in new concrete manufacturing, however, leads to a decrease in concrete's strength characteristics. This reduction rises with the rise in the percentage of recycled aggregates used in concrete, which led us to conduct this research, which aims to study the properties of concrete containing recycled aggregates in proportions (0% -50% -100%) with the addition of steel fibers in proportions (0.5% -1% -1.5%) and study the effect of this on the behavior of concrete.The results showed an increase in concrete resistance to pressure when using fibers by (0.5-1%), while it decreased when using the ratio 1.5%.The experimental results also showed an increase in the splitting tensile strength, the flexural strength, and the modulus of elasticity by increasing the steel fibers ratios.